2010
DOI: 10.1186/cc8865
|View full text |Cite
|
Sign up to set email alerts
|

A disparity between physician attitudes and practice regarding hyperglycemia in pediatric intensive care units in the United States: a survey on actual practice habits

Abstract: IntroductionHyperglycemia is common in critically ill patients and is associated with increased morbidity and mortality. Strict glycemic control improves outcomes in some adult populations and may have similar effects in children. While glycemic control has become standard care in adults, little is known regarding hyperglycemia management strategies used by pediatric critical care practitioners. We sought to assess both the beliefs and practice habits regarding glycemic control in pediatric intensive care unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 26 publications
0
30
0
1
Order By: Relevance
“…7 Hence most of the pediatric critical care physicians would care to avoid stress hyperglycemia but worry about the hypoglycemia encountered while attempting for a tight glycemic control. 10,11 Mechanical ventilation, vasoactive infusions, renal replacement therapies, cardiopulmonary bypass and extracorporeal life support, therapeutic hypothermia, prolonged immobility, nutrition support practices, and the use of medications are all known to mediate development of SH in critical illness. 12 In this study 58 % were females and 42% were males.…”
Section: Discussionmentioning
confidence: 99%
“…7 Hence most of the pediatric critical care physicians would care to avoid stress hyperglycemia but worry about the hypoglycemia encountered while attempting for a tight glycemic control. 10,11 Mechanical ventilation, vasoactive infusions, renal replacement therapies, cardiopulmonary bypass and extracorporeal life support, therapeutic hypothermia, prolonged immobility, nutrition support practices, and the use of medications are all known to mediate development of SH in critical illness. 12 In this study 58 % were females and 42% were males.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys have shown that there is wide variation in physicians' beliefs and practices with respect to BG control in critically ill children. 22,29,30 This probably represents the current usual practice of glucose control in critically ill children with variations of protocols used and BG measurements from different blood compartments using BG meters. 12,13 The present study included patients from two ICUs with a broad mix of diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] It is unclear as to what extent these recommendations have been adopted by pediatric intensivists. 46,47 By stratifying glucose data according to the number of glucose values above each cutoff, the prevalence of hypo-and hyperglycemia was identified more accurately and the influence of spurious "one-time" glucose measurements was removed. Similar to previous reports, increasing glucose values were associated with increasing total hospital and PICU LOS with the greatest LOS reported in patients above the 200 mg/dl cutoff.…”
Section: Discussionmentioning
confidence: 99%